STRATEGI PENGEMBANGAN SARANA DAN PRASARANA EKOWISATA KRUENG JALIN KOTA JANTHO - Fachrurrazi Fachrurrazi; Sofyan M. Saleh; Izziah Izziah (Prodi Magister Teknik Sipil Unsyiah, 2022)
At present, Kota Jantho sub-district has only one representative tourist attraction with visitors' desires, which is Jantho Panorama Park, which was only developed in 2021. Therefore, the tourist attraction Krueng Jalin that is not properly managed must be developed into an eco-tourism object, so that Jantho City has multiple tourism alternatives that are representative of the population and can have an impact on the economic improvement of the region. This study aims to determine the strategy for developing ecotourism facilities and infrastructure in Krueng Jalin. This study uses a qualitative method approach through interviews and quantitative methods through questionnaires. Resource people and respondents targeted to up to 8 people. Data analysis used Strengths Weaknesses Opportunities Threats (SWOT). The results show that the Krueng Jalin ecotourism facility and infrastructure development strategy that needs to be implemented is to develop the potential for ecotourism packages and propose ecotourism facility and infrastructure development activities in Krueng Jalin to the regional government to participate in Local communities are involved in the planning and construction of ecotourism facilities and infrastructure in Krueng Jalin. Krueng Jalin, established an ecotourism management agency, developed decent work programs or business opportunities for local communities, involved the community in ecotourism management, established zones and visiting hours, provided environmental education to local communities and visitors, arranged income sharing and ecotourism marketing products.